2020
DOI: 10.1021/acsnano.0c09422
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterning of Living Cells with Extracellular DNA Programs

Abstract: Reactive extracellular media focus on engineering reaction networks outside the cell to control intracellular chemical composition across time and space. However, current implementations lack the feedback loops and out-of-equilibrium molecular dynamics for encoding spatio-temporal control. Here, we demonstrate that enzyme-DNA molecular programs combining these qualities are functional in an extracellular medium where human cells can grow. With this approach, we construct an internalization program that deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 64 publications
0
24
1
Order By: Relevance
“…We have demonstrated that greater DTT concentrations improve the responsiveness of the DNA program in the presence of serum. However, since high levels of [DTT] decrease cell 10 viability, as they transiently activate endoplasmic reticulum stress 27 and cause cell detachment, 3 we decided to further increase the biocompatibility of our buer to mitigate cytotoxicity (although the introduction of FBS already partially attenuates the adverse eect of DTT, Figure S16). To do so, we increased the concentration of the cell culture medium (from 0.5x to 0.89x), we removed non-critical PEN buer components and lowered the concentration of magnesium (SI Section 3) to create a new buer that we named Cell+ buer.…”
Section: Increasing the Biocompatibility Of The Buermentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated that greater DTT concentrations improve the responsiveness of the DNA program in the presence of serum. However, since high levels of [DTT] decrease cell 10 viability, as they transiently activate endoplasmic reticulum stress 27 and cause cell detachment, 3 we decided to further increase the biocompatibility of our buer to mitigate cytotoxicity (although the introduction of FBS already partially attenuates the adverse eect of DTT, Figure S16). To do so, we increased the concentration of the cell culture medium (from 0.5x to 0.89x), we removed non-critical PEN buer components and lowered the concentration of magnesium (SI Section 3) to create a new buer that we named Cell+ buer.…”
Section: Increasing the Biocompatibility Of The Buermentioning
confidence: 99%
“…Although we found an average ∼2-fold reduction in growth rate compared to the control, a ∼2-fold increase in viable cell number after 48 h was achieved compared to previously reported experimental conditions in the absence of FBS (Kin buer). 3 To stress the importance of developing serum-compatible DNA/enzyme programs, we studied the growth of human embryonic kidney 293 cells (HEK 293 cell line), as their behaviour (e.g. signalling pathways) is signicantly aected by serum starvation.…”
Section: Increasing the Biocompatibility Of The Buermentioning
confidence: 99%
See 3 more Smart Citations